2023
DOI: 10.1080/02670836.2022.2141874
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness – the key for roll bonding aluminium

Abstract: In this study, the commercially pure aluminium is roll bonded at ambient temperatures. The effect of surface roughness and roll speed on the bond strength is evaluated by using the lap shear test. It is observed that the bond strength increased considerably with increasing surface roughness. The deformation caused owing to scratch brushing changed the surface roughness profile, which is the salient reason for the bond strength variation. Continuous striations with peaks and valleys of small-scale heights are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…• Adhesive and abrasive wear behaviors are observed, with the weld zone generally exhibiting superior wear resistance compared to base composites [39][40][41].…”
Section: Wear Propertiesmentioning
confidence: 99%
“…• Adhesive and abrasive wear behaviors are observed, with the weld zone generally exhibiting superior wear resistance compared to base composites [39][40][41].…”
Section: Wear Propertiesmentioning
confidence: 99%
“…25 reported that SSW adhesion through rolling increases as the initial roughness of the sheets rises, as confirmed by Biradar and Rijesh. 26 Bay 27,28 confirmed that SSW occurs locally, at the contact of ‘high spots’ in the two surfaces to be joined; in addition, a modified ‘film theory’ was proposed, where the surface cracks before the extrusion would occur through the ‘…fracture of the work hardened surface layer produced by scratch brushing and exposure of the base metal’. This surface layer is denominated ‘cover layer’ and the ‘… fracture of a brittle cover layer’ is mentioned, in the so-called C–C mechanism.…”
Section: Introductionmentioning
confidence: 98%